Implementasi Program Literasi Numerasi Kampus Mengajar Angkatan 7 di SDI Matsaratul Huda Pamekasan - Aisyah Bella; Faridatus Zulfa; Maghfiroh Maghfiroh; Septi Dariyatul Aini; Fetty Nuritasari (Institut Teknologi dan Bisnis Semarang, 2024)
The Teaching Campus Program provides students with the opportunity to study outside campus and contribute directly to the world of education, by becoming partners with teachers in developing creative, innovative and fun learning strategies. Through the Teaching Campus program, students can develop teaching skills and contribute positively to the world of education and help improve students' literacy and numeracy skills. The method applied involves active participation of students together with teachers in designing work programs that are creative, effective and interesting by utilizing various existing media and learning resources to increase student interest, activity and understanding, especially literacy and numeracy. . This service activity was carried out at SDI Matsaratul Huda, Pamekasan District, Pamekasan Regency, East Java. This activity was carried out for 4 months from 26 February 2024 to 15 June 2024. The final results of the Teaching Campus program were significantly able to improve the literacy and numeracy skills of students at SDI Matsaratul Huda. Apart from that, students' interests, activities and learning outcomes also increase with the campus teaching program.